Dynamic cities: Location-based accessibility modelling as a function of time. (June 2018) - Järv, Olle; Tenkanen, Henrikki; Salonen, Maria; Ahas, Rein; Toivonen, Tuuli
Abstract: The concept of accessibility – the potential of opportunities for interaction – binds together the key physical components of urban structure: people, transport and social activity locations. Most often these components are dynamic in nature and hence the accessibility landscape changes in space and time based on people's mobilities and the temporality of the transport network and activity locations (e.g. services). Person-based accessibility approaches have been successful in incorporating time and space in the analyses and models. Still, the more broadly applied location-based accessibility modelling approaches have, on the other hand, often been static/atemporal in their nature. Here, we present a conceptual framework of dynamic location-based accessibility modelling that captures the dynamic temporality of all three accessibility components. Furthermore, we empirically test the proposed framework using novel data sources and tools. We demonstrate the impact of temporal aspects in accessibility modelling with two examples: by investigating food accessibility and its spatial equity. Our case study demonstrates how the conventional static location-based accessibility models tend to overestimate the access of people to potential opportunities. The proposed framework is universally applicable beyond the urban context, from local to global scale and on different temporal scales and multimodal transport systems. It also bridges the gap between location-based accessibility and person-based accessibility research. Highlights: Current models of a location-based accessibility are often atemporal in nature. Locations of people, transport and service supply may change drastically over 24 h. A framework to fully integrate time in a location-based accessibility is proposed. Conventional atemporal accessibility models tend to overestimate spatial access. Potential novel data sources for accessibility modelling is identified and applied.